Sync to link: Endorphin-mediated synchrony effects on cooperation - Lang, Martin; Bahna, Vladimír; Shaver, John H; Reddish, Paul; Xygalatas, Dimitris (Biological psychology, 2017)
Behavioural synchronization has been shown to facilitate social bonding and cooperation but the mechanisms through which such effects are attained are poorly understood. In the current study, participants interacted with a pre-recorded confederate who exhibited different rates of synchrony, and we investigated three mechanisms for the effects of synchrony on likeability and trusting behaviour: self-other overlap, perceived cooperation, and opioid system activation measured via pain threshold. We show that engaging in highly synchronous behaviour activates all three mechanisms, and that these mechanisms mediate the effects of synchrony on liking and investment in a Trust Game. Specifically, self-other overlap and perceived cooperation mediated the effects of synchrony on interpersonal liking, while behavioural trust was mediated only by change in pain threshold. These results suggest that there are multiple compatible pathways through which synchrony influences social attitudes, but endogenous opioid system activation, such as β-endorphin release, might be important in facilitating economic cooperation.
Keywords: dospělí; endorfiny; Interpersonal Relations; práh bolesti; Endorphins; interpersonální vztahy; Female; Pain Threshold; mužské pohlaví; mladý dospělý; lidé; Attitude; ženské pohlaví; kooperační chování; Humans; Trust; postoj; Male; Cooperative Behavior; Young Adult; Adult; důvěra